Individualität und Kollektivität Deutsche und japanische Perspektiven auf Recht, Kultur und Rechtskultur - Wolff, Daniel; Kaspar, Johannes; Kurishima, Tomoaki (Mohr Siebeck, 2025)
What is the relationship between the individual and the collective, between individuality and collectivity, in German and Japanese law? This volume delves into this question from both intra- and interdisciplinary perspectives, seeking to uncover the individualistic and collectivistic dimensions inherent in each legal system.
PublicationDate: 20250305
Keywords: Persönlichkeitsrecht -- Soziologie -- Gesellschaft -- Grundrechte -- rational choice theory -- Menschenbild -- Gemeinschaft -- Kodex für die elektronische Kommunikation -- Interessenabwägung -- EWG -- Rechtsphilosophie -- Rechtsgeschichte -- Ausländisches Recht, Rechtsvergleichung